Attenuation of neural responses in subthalamic nucleus during internally guided voluntary movements in Parkinson’s disease - Filyushkina, Veronika; Belova, Elena; Usova, Svetlana; Tomskiy, Alexey; Sedov, Alexey (Frontiers in Human Neuroscience, 2022)
The proposed models of segregated functional loops describe the organization of motor control over externally triggered (ET) and internally guided (IG) movements. The dopamine deficiency in Parkinson’s disease (PD) is considered to cause a disturbance in the functional loop regulating IG movements. At the same time, the neural mechanisms of movement performance and the role of basal ganglia in motor control remain unclear.The aim of this study was to compare neuronal responses in the subthalamic nucleus (STN) during ET and IG movements in PD. We found and analyzed 26 sensitive neurons in 12 PD patients who underwent surgery for implantation of electrodes for deep brain stimulation. We also analyzed the local field potentials (LFP) of the STN of six patients during the postoperative period. Patients were asked to perform voluntary movements (clenching and unclenching the fist) evoked by verbal command (ET) or self-initiated (IG). We showed heterogeneity of neuronal responses and did not find sensitive neurons associated with only one type of movement. Most cells were characterized by leading responses, indicating that the STN has an important role in movement initiation. At the same time, we found attenuation of motor responses during IG movement vs. stable responses during ET movements. LFP analysis also showed attenuation of beta desynchronization during multiple IG movements.We propose that stable neuronal response to ET movements is associated with the reboot of the motor program for each movement, while attenuation of responses to IG movement is associated with single motor program launching for multiple movements.